An exploratory study on the dımensıons of employer brandıng - Kuşçu, Aslı; Yolbulan Okan, Elif (Öneri Dergisi, 2010)
This paper aims to be a fresh view to employer branding, which is a new concept in the business, marketing and HR worlds and in Turkey. This study aims to make a brief comparison between the viewpoints of Turkish professionals and university students to the dimensions of attractiveness in employer branding. The results of this exploratory study will have preliminary findings that will be important for many companies aiming to attract and maintain talent in order to build a corporate brand name and satisfy their stakeholders. The difference between undergraduate students’ and professionals’ perceptions about dimensions of employer attractiveness is investigated in this study. In macro senses, this paper is an example of marketing being a multidisciplinary science. It does not only serve for branding a product but it also has implications in human resource management or in finance or other departments of the company.
İşveren markalaşmasının boyutları üzerine keşifsel bir çalışma
Keywords: Employer Branding, Internal Marketing, Corporate Branding, Human Resources. - İşveren Markalaşması, Şirket Markaları, İç Pazarlama, İnsan Kaynakları.